How important are holiday trips in preventing loneliness? Evidence for people without and with self-reported moderate and severe disabilities - Pagán-Rodríguez, Ricardo Braulio (Taylor & Francis, 2019)
This study analyzes the relationship between holiday trips and loneliness for people without and with self-reported disabilities (differentiating between moderate and severe disabilities limiting their daily activities) in Germany. Since loneliness is not only observed at older ages, we are particularly interested in exploring possible age differences in this relationship. Using data taken from the German Socio-Economic Panel for the year 2013 and applying a three-item version of the UCLA Loneliness Scale, we found that holiday trips contribute to reducing the levels of loneliness reported by all individuals, and that this reduction is even higher for people with self-reported disabilities (males and females) who are severely limited in their daily activities. However, the positive effects of holiday trips on loneliness did differ by age groups. The loneliness scores of people who have limiting disabilities in the 40– 64 age group showed the greatest reduction as compared to those reported for people without self-reported disabilities. From a public policy and management perspective, the promotion of full access and participation of people with disabilities as active travellers within the tourism industry must be aimed at reducing their levels of loneliness and increasing their social tourism opportunities and experiences
Política de acceso abierto tomada de: https://openpolicyfinder.jisc.ac.uk/id/publication/19859
Keywords: Vacaciones - Aspectos psicológicos; Turismo - Aspectos sociales; UCLA loneliness scale; Health status; Daily activities